THE CHALLENGES FACED BY ENGLISH LANGUAGE LEARNERS IN DIFFERENT EDUCATIONAL CONTEXTS (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In addition to limited vocabulary and pronunciation, ESL students may also struggle with listening and speaking skills. Without strong listening and speaking skills, your students may have difficulty participating in class discussions, understanding lectures, and expressing themselves in English.